2020
DOI: 10.17305/bjbms.2020.5016
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of gut microbiota in inflammatory bowel disease: Current therapies and potential for microbiota-modulating therapeutic approaches

Abstract: There is a growing body of evidence reinforcing the unique connections between the host microbiome, health and diseases. Due to the extreme importance of the symbiotic relationship between the intestinal microbiome and the host, it is not surprising that any alteration in the gut microbiota would result in various diseases, including inflammatory bowel disease (IBD), Crohn’s disease (CD) and ulcerative colitis (UC). IBD is a chronic, relapsing-remitting condition that is associated with significant morbidity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 148 publications
0
29
0
1
Order By: Relevance
“…A great number of previous studies have demonstrated that the gut microbiota or modulation of the gut microbiota associated with development or control of colitis [24][25][26][27][28], although the precise knowledge regarding the speci c bacterial species and the active metabolites that can be used for the clinical management of colitis remains to be de ned. In the current study, we not only demonstrated the key role of the gut microbes and metabolites in mediation of SH anti-colitis effect in a mouse model of colitis, but also identi ed A. onderdonkii as a novel bene cial microorganism that possessed an anti-colitis activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of previous studies have demonstrated that the gut microbiota or modulation of the gut microbiota associated with development or control of colitis [24][25][26][27][28], although the precise knowledge regarding the speci c bacterial species and the active metabolites that can be used for the clinical management of colitis remains to be de ned. In the current study, we not only demonstrated the key role of the gut microbes and metabolites in mediation of SH anti-colitis effect in a mouse model of colitis, but also identi ed A. onderdonkii as a novel bene cial microorganism that possessed an anti-colitis activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A tremendous amount of extensive research work has been done in the last decades, and has revealed that the gut microbiota dysbiosis can be associated with many pathologies within the human body [ 21 ], such as periodontitis and caries [ 23 , 24 ], various metabolic disorders [ 25 27 ], chronic inflammatory bowel syndromes [ 28 ], cardiovascular diseases (CVD) [ 29 , 30 ], cancer [ 31 , 32 ], as well as chronic kidney diseases (CKD) [ 33 , 34 ]. The extent to which gut microbiota dysbiosis may exert this systemic control and cause the induction of a given pathology depends on the functionality of gut barrier and the maturity of the immune system of the recipient [ 35 ].…”
Section: Human Microbiome and Microbiota Dysbiosis In Human Diseasesmentioning
confidence: 99%
“…The two most common, namely, Crohn disease (CD) and ulcerative colitis (UC), are associated with disturbance of the intestinal microbiota (dysbiosis) [ 1 , 2 ]. The gut microbiota plays an important role in the regulation of intestinal homeostasis, including maturation and the functioning of epithelial and immune cells [ 3 ]. Recent studies have emphasized that dysbiosis is related to the pathogenesis of IBD and may exacerbate the course of the disease [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota plays an important role in the regulation of intestinal homeostasis, including maturation and the functioning of epithelial and immune cells [ 3 ]. Recent studies have emphasized that dysbiosis is related to the pathogenesis of IBD and may exacerbate the course of the disease [ 2 , 3 ]. Changes in the gut microbiota have been frequently observed in patients with IBD, with certain changes clearly linked to either CD or UC: the most consistent alteration is a reduction in Firmicutes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%